Technical Considerations in Plastibell Circumcision in Neonates and Infants - Muhammad Tahir Ghani, Muhammad Tahir Ali, Azad Ali Lashari, Hafiz Muhammad Ijaz-Ul-Haq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out efficacy of plastibell circumcision and to establish certain technical considerations to minimize complications. Study design: Cross-sectional Descriptive study Place and duration of study: Department of Surgery, Aero Hospital Hassan Abdal from 1st September 2016 to 31st August 2020. Method: Total of 400 infants and neonates were included in present study. Children was taken upto six months of age and 1% lignocaine was used as a source of local anesthesia. Plastibell was used for circumcision under strict aseptic conditions. Parents were allowed to take child home after half hour of retention in the hospital and follow up done after one week of circumcision. Parents were given telephonic access to surgeon during this week. During follow up baby was examined, results recorded and complications were treated if any. Results: Ring block using 1% lignocaine provided adequate pain relief in neonates and infants. There were 345 boys were brought for circumcision during first month of their life while 55 were infants between one to six months of age. Six patients had post-operative bleeding during immediate post op period and two patients presented after 12 hours with bleeding which needed removal of plastibell and maintenance of hemostasis. The mean time of plastibell detachment was 06 days (range 03-12 days). Plastibell was ctuck in few patients which needs to be removed early. Paracetamol was also used post-operatively as an oral analgesia and provided adequate pain relief. Two patients presented with infection after plastibell detachment. The foreskin was removed in every boy except one. Handling of the babies was easy for mothers. Conclusion: Plastibell proved to be an effective method of circumcision provided few technical points like size of plastibell, use of bipolarcautery, hemostasis of frenular area, and threading around plastibell are properly taken care off. Keywords: Circumcision, Plastibell, Neonate, Infant, Lignocaine, Frenular, Foreskin